From low to high gear: there has been a paradigm shift in our understanding of evolution1. (26th November 2018) - Reznick, David N.; Losos, Jonathan; Travis, Joseph
Abstract: Experimental studies of evolution performed in nature and the associated demonstration of rapid evolution, observable on a time scale of months to years, were an acclaimed novelty in the 1980–1990s. Contemporary evolution is now considered ordinary and is an integrated feature of many areas of research. This shift from extraordinary to ordinary reflects a change in the perception of evolution. It was formerly thought of as a historical process, perceived through the footprints left in the fossil record or living organisms. It is now seen as a contemporary process that acts in real time. Here we review how this shift occurred and its consequences for fields as diverse as wildlife management, conservation biology, and ecosystems ecology. Incorporating contemporary evolution in these fields has caused old questions to be recast, changed the answers, caused new and previously inconceivable questions to be addressed, and inspired the development of new subdisciplines. We argue further that the potential of contemporary evolution has yet to be fulfilled. Incorporating evolutionary dynamics in any research program can provide a better assessment of how and why organisms and communities came to be as they are than is attainable without an explicit treatment of these dynamics.